Los intelectuales en los intersticios de la política (Brasil, 1940-45) - de Melo, Ana Amélia de Moura Cavalcante (Diálogos Latinoamericanos, 2012)
Since the 1920 literature in Brazil was designed by a group of intellectuals as a commitment to cultural life of the country. Mario de Andrade and São Paulo's modernist influence the formation of the writers on that commitment in the years 30 and 40 are generalized. The literature that is written in this period central theme is the social and political drama, very similar to the sociological and historical essays. This article seeks to reflect on such Brazilian intellectuals organize and act through the Brazilian Association of Writers. Try to understand how they perceive the national reality, which are developed and analyzes how they think their role in society